Performing Salome in the Pacific. Three works by Yuki Kihara - Franco, Susanne (Mimesis Journal, 2024)
The essay explores three works by the Japanese-Sāmoan interdisciplinary artist, researcher, and curator Yuki Kihara. More specifically it delves into Kihara’s reenactment of the taualuga, a traditional Sāmoan dance, as well of the mythological figure Salome, who wielded dance as a tool for political manipulation and became Kihara’s evolving alter-ego since 2002. Kihara’s performances and videos, particularly Siva in Motion and Galu Afi, address themes of mourning over colonialism’s impact on Pacific peoples, in the wake of the environmental crisis. Drawing on influences from ethnographic photography and Western theatrical traditions, Kihara’s works offer a critical perspective on identity and power dynamics, highlight the fluidity of gender and cultural identity, and invite audiences to reframe historical narratives and challenge colonial representations. Her performances also contribute to the most recent critique of the long-standing canonical approach to dance modernism as limited geographically to Western culture and to rethink it rather as a transtemporal and trans-local phenomenon. Lastly, Kihara’s engagement with the Sāmoan concept of vā—meaning the collapsing of time and space—contribute to the decolonisation of museums by engaging with alternative forms of historical representation and creating a conceptual space where historical pasts, community memory, and embodied knowledge coexist and interact.